LOAD DEFLECTION OF ENGINEERED CEMENTITIOUS COMPOSITES (ECC) OF REINFORCED SLAB - SULAIMAN, NUR SHAZMEEN (IRC, 2016)
This research paper is mainly focused on investigating the application of new type of concrete material named Engineered Cementitious Composites (ECC) in reinforced two way slab. The development of Engineered Cementations Composites (ECC) over the last decade since its invention in the early 1990’s suggested that the compressive strength of reinforcement concrete increases as well as its tensile strength as it capable to transform from tension softening properties of the concrete into strain hardening. In order to prove it, Johansen’s method is used to calculate the ultimate moment. Total of ten two-way typed of ECC reinforced slabs with fixed dimension of 980mm x 500mm (length and width) with varies slab thicknesses and number of reinforcement steel are carried out. These variables could hold the purpose of allowing any way of possibilities in achieving the reliability of yield line methods towards the ECC reinforced slab. The slab is set up with pin-pin boundary condition associated with uniform distributed type of loading and after testing, the results will give the reading of load capacity and its deflection. Further investigation can be made by calculating the load ratio of the ECC reinforced slab where it achieved the main objective of this research. Load ratio with equal to 1 indicates that the yield line method is applicable. Otherwise, recommendations can be made.